Gangs Born Out of Civil War: Factors Leading to the Creation of MS-13 and 18th Street Gang - Casales, Robert (Colloquium: The Political Science Journal of Boston College, 2018)
Throughout the past decade, El Salvador has often been referred to as “The Murder Capital of the World.” The main contributors to the unprecedented growth rate of homicide in El Salvador are the country’s two most notorious gangs, MS-13 and 18th Street Gang, both of which were formed following El Salvador’s bloody civil war. In this paper, Casales explains how the violence during the Salvadoran Civil War, the social and political conditions in the United States, the failed reconstruction efforts made by the Salvadoran Government, and the influx of deported gang members all led to the establishment of these two murderous gangs. Finally, Casales concludes with the recommendation that the Salvadoran Government should address their gang violence epidemic with a social approach involving local institutions such as the church rather than the current “Iron Fist” policy.